Comparing walking and running in persistence hunting. Issue 172 (November 2022) - Hora, Martin; Pontzer, Herman; Struška, Michal; Entin, Pauline; Sládek, Vladimír
Abstract: It has been proposed that humans' exceptional locomotor endurance evolved partly with foraging in hot open habitats and subsequently about 2 million years ago with persistence hunting, for which endurance running was instrumental. However, persistence hunting by walking, if successful, could select for locomotor endurance even before the emergence of any running-related traits in human evolution. Using a heat exchange model validated here in 73 humans and 55 ungulates, we simulated persistence hunts for prey of three sizes (100, 250, and 400 kg) and three sweating capacities (nonsweating, low, high) at 6237 combinations of hunter's velocity (1–5 m s −1, intermittent), air temperature (25–45 °C), relative humidity (30–90%), and start time (8:00–16:00). Our simulations predicted that walking would be successful in persistence hunting of low- and nonsweating prey, especially under hot and humid conditions. However, simulated persistence hunts by walking yielded a 30–74% lower success rate than hunts by running or intermittent running. In addition, despite requiring 10–30% less energy, successful simulated persistence hunts by walking were twice as long and resulted in greater exhaustion of the hunter than hunts by running and intermittent running. These shortcomings of pursuit by walking compared to running identified in our simulations could explain why there is only a single direct description of persistence hunting by walking among modern hunter-gatherers. Nevertheless, walking down prey could be a viable option for hominins who did not possess the endurance-running phenotype of the proposed first persistence hunter, Homo erectus . Our simulation results suggest that persistence hunting could select for both long-distance walking and endurance running and contribute to the evolution of locomotor endurance seen in modern humans.